(untitled) (Community Based Medical Journal, 2013)
To examine the effect of timing at which women admitted either in active or latent phase of spontaneous labour on subsequent outcome. This cross-sectional study was conducted at labour ward, department of Obstetrics and Gynaecology, BSMMU hospital, Dhaka, Bangladesh, from August 2007 to November 2007, where data were collected prospectively. A total of 60 women with term, singletone pregnancy, cephalic presentation with spontaneous onset of labour admitted in labour either in active or latent phase were selected for evaluation. Patients with any medical or obstetric complications, rupture of membrane, antenatally diagnosed foetal anomalies or death and with prior caesarean section were excluded from the study. Patients with cervical dilatation at less than 4cm were categorized as latent phase and were in group I. On the other hand, patients with cervical dilatation of 4 cm or more were marked as in active phase and were allocated in group II. Baseline characteristics were compared. Outcome differences were compared using chi-square(X2) test, t test, fishers exact test, A p value <0.05 considered significant. Duration of labour, mode of delivery, indication for caesarean section, need for oxytocin, labour analgesia, Apgar score <7, birth weight of baby, maternal PPH and postpartum hospital stay. A total of 60 patients were enrolled during the study period. Of them 35 patients (58.3%)were in group I and 25 patients (41.7%) in group II. Duration of labour was more in early admitted group compared to late admitted group (mean± SD 17.0 ± 2.8 vs 14.3 ± 2.4). Latent phase women needed more caesarean delivery than active phase women (62.9% vs 28.0%). Dystocia was the main indication for caesarean delivery in the present study which was 68.2% and 28.6% in early and late admitted group respectively. Second commonest indication for caesarean section was foetal distress (6 in group I and 5 in group II). Oxytocin for augmentation was used in 62.9% in group I and 56.0% in group II and nulliparae women were the one who needed more augmentation (40.0% in group I, 36.0% in group II). Mean foetal weight between two groups did not reach any significant difference (p>0.05). Apgar score <7 shows insignificant difference between two groups. PPH was found in 5.7% cases and all were from group I. Total postpartum hospital stay was significantly longer in group I than group II (p<0.05). t is shown that early admission to the hospital in low-risk women may negatively affect the outcome of labour and are at increased risk of prolonged labour, more need for analgesia, increased rate of caesarean section, increased PPH and postpartum hospital stay. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14177 Community Based Medical Journal Vol.2(1) 2013 21-28